Malignant Gastrointestinal Neuroectodermal Tumor: A New Kid on the Block?. Issue 5 (21st September 2022) - Morani, Ajaykumar C.; Ramani, Nisha S.; Yedururi, Sireesha; Prasad, Srinivasa R.
Abstract: Also referred to as "osteoclast-rich, clear cell sarcoma–like tumor of the gastrointestinal tract (CCSLGT), " malignant gastrointestinal neuroectodermal tumor is a newly described, rare, aggressive sarcoma that commonly arises in the small bowel, stomach, and colon. Histogenesis is likely from an autonomous nervous system–related primitive cell of neural crest origin. The hallmark genetic finding of EWS-CREB1 or EWS-ATF1 fusion transcripts clinches the diagnosis. Annular constrictive lesions tend to be smaller, show homogenous contrast enhancement on computed tomography, and may present with bowel obstruction. Larger, expansile masses tend to be exophytic and show heterogeneous contrast enhancement. Surgical resection is the mainstay of treatment. Frequent recurrences, metastases, and death from disease in 75% of patients portend a poor prognosis. Targeted chemotherapy based on specific tumor pathways is being developed.